ABC Classification Analysis for Optimizing Inventory Management of Best-Selling Products in Employee Cooperatives PT. Indofood CBP Sukses Makmur Tbk - Imas Widowati; Muhammad Fariedz Fauzan Hilman (Sekolah Tinggi Teknologi Wastukancana, 2026)
Employee cooperatives play a strategic role in fulfilling members' daily needs; however, their success depends heavily on the effectiveness of inventory management. This study aims to identify best-selling products (fast-moving items), analyze consumer demand patterns, and design an optimal inventory control strategy at the Koperasi Karyawan Aneka Pangan Nusantara (KOPKANUS) PT. Indofood CBP Sukses Makmur Tbk, Purwakarta. The method employed was quantitative analysis of sales data from the period of June to August 2025, using ABC Classification Analysis. The results indicate that five main products — Indomie Goreng Spesial, Indomie Ayam Bawang, Ichi Ocha 350 ml, Indomie Soto Mie, and Indomie Bangladesh — belong to Class A, contributing 88.5% of the total sample revenue of IDR 98,154,600. Meanwhile, Class B products contributed 11.4% and Class C products contributed only 0.13%. Sales trends showed an increase from 8,461 units in June to 9,930 units in August 2025, yet accompanied by a high frequency of stockouts for Class A products, particularly toward the end of each month. Based on these findings, the cooperative is advised to implement a priority-based inventory control system according to product class, establish safety stock and reorder points (ROP) for Class A products, and conduct periodic evaluations of Class C products. The implementation of these recommendations is expected to reduce stockout occurrences, improve the availability of best-selling products, and optimize overall sales performance.